Mullite-2c – a natural polytype of mullite - S. Lenz; J. Birkenstock; L. A. Fischer; L. A. Fischer; H. Schneider; R. X. Fischer (European Journal of Mineralogy, 2020)
A single crystal (∼ 20 µm × 20 µm × 330 µm) of mullite-2c, a natural polytype of mullite, was separated from a radially grown cluster of acicular crystals from Ettringer Bellerberg (Quarternary Eifel volcanic fields, Germany). The chemical composition determined from electron microprobe analysis (EMPA) is Na0.01Mg0.05Al8.52<msubsup>Fe0.293+</msubsup>Si3.13Ti0.02O19.55<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="197pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="c50cca7629249c7ad5e395c36083603f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-32-235-2020-ie00001.svg" width="197pt" height="17pt" src="ejm-32-235-2020-ie00001.png"/></svg:svg>, corresponding to x=0.22(8) in the generalised mineral formula <msubsup>My+</msubsup><msubsup>Mgz2+</msubsup><msubsup>M8+4x+y-2z3+</msubsup><msubsup>M4-4x-y+z4+</msubsup>O20-2x<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="178pt" height="18pt" class="svg-formula" dspmath="mathimg" md5hash="519e8c7792d94a260628f24967e14818"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-32-235-2020-ie00002.svg" width="178pt" height="18pt" src="ejm-32-235-2020-ie00002.png"/></svg:svg>. Only Fe3+ as foreign cation was considered in the refined structure model, partially replacing Al3+ in the octahedral chains. A crystal of a similar type, though exhibiting a significantly different composition with x=0.02, was first described in 2015, tentatively named “sillimullite” by Fischer et al. (2015). This crystal and our new sample have similar structural properties, now classified as a polytype of mullite, designated mullite-2c. Single-crystal X-ray diffraction showed that the mullite-2c crystal investigated here exhibits partial Si ∕ Al ordering in the double chains of (Si,Al)O4 tetrahedra in contrast to the sample described in 2015 as being completely ordered. The ordering in mullite-2c results in a doubled c lattice parameter with respect to mullite. It crystallises in space group Pnam, with cell parameters for the new sample of a=7.5432(5) Å, b=7.7048(5) Å, c=5.7965(3) Å, V=336.89(6) Å3 and Z=1. X-ray powder diffraction data are presented with a detailed discussion of the differences between the diffraction patterns of sillimanite, mullite and mullite-2c. Crystals of mullite-2c are translucent to lightly violet, they possess a vitreous lustre and the calculated density is 3.199 g cm−3. The optical character is biaxial (+), with refractive indices determined by spindle-stage microscopy of nx=1.6673, ny=1.6687 and nz=1.680(4) (adjusted to conform to 2VZ=39(4)∘). Applying the Gladstone–Dale approach, the compatibility index is 0.007, representing superior compatibility. In terms of chemical composition and structural features mullite-2c is an outstanding example of mullite-type compounds falling into the postulated miscibility gap between sillimanite and mullite. Its crystal structure combines characteristics from both mullite (oxygen vacancies, triclusters of tetrahedral building units) and sillimanite (high degree of Si ∕ Al ordering in the tetrahedral building units, causing the doubled c parameter). The lattice parameters (normalised to 1c) of the new sample lie between those of sillimanite and 3 / 2 mullite; the chemical composition is close to 3 / 2 mullite and thus differs significantly from the silica-rich composition of the species previously determined by Fischer et al. (2015), indicating a relatively large compositional variation.